Pecat amagat és mitg perdonat.... La polèmica entre mossèn Gudiol i Antoni Bulbena arran de les edicions bibliòfiles de llibres eròtics. - DOMÈNECH, ALBERT (Scripta, 2014)
In December 1911 appeared in the local press in Vic (a town near Barcelona) an article that raised an uproar in the bibliophile circles all over Catalonia. A priest (an Art historian and great moralist) accused a well-known editor of fine books, without naming him, of editing luxury books of pornographic content. This anecdote serves us to find out who this editor was, how much truth there was in the «accusation» and how the censored editor took the fact of being exposed to public shame. The correspondence between the priest and the editor, facilitated by a common friend, helps us analyze the arguments of both parties. We can grasp how the vast frame that embraces love literature to clearly pornographic works was perceived, both from the most conservative moral to a moderate free-thinking perspective.